Antifungal azaphilones from the fungus Chaetomium cupreum CC3003 - Kanokmedhakul, Somdej; Kanokmedhakul, Kwanjai; Nasomjai, Pitak; Louangsysouphanh, Sysavad; Soytong, Kasem; Isobe, Minoru; Kongsaeree, Palangpon; Prabpai, Samran; Suksamrarn, Apichart (My University, 2006)
Three new azaphilones named rotiorinols A-C (1-3), two new stereoisomers, (-)-rotiorin (4) and epi-isochromophilone II (5), and a known compound, rubrorotiorin (6), were isolated from the fungus Chaetomium cupreum CC3003. Structures were established on the basis of spectroscopic evidence. The absolute configuration of 1 was determined by the modified Mosher's method along with an X-ray analysis of its acetate derivative, as well as by chemical transformation. Compounds 1, 3, 4, and 6 exhibited antifungal activity against Candida albicans with IC50 values of 10.5, 16.7, 24.3, and 0.6 μg/mL, respectively. © 2006 American Chemical Society and American Society of Pharmacognosy.